Red mud industrial waste translated into green electricity production by innovating an ingenious process based on Hydroelectric Cell. Issue 2 (April 2022) - Kotnala, R.K.; Das, Rojaleena; Shah, Jyoti; Sharma, Sanjeev; Sharma, C.; Sharma, P.B.
Abstract: Globally a prominent hazardous industrial waste red mud (RM) residue is released in million tons everyday from alumina refinery. One of the best options to utilize red mud is the fabrication of Hydroelectric Cell (HEC) to produce green electricity, has been reported. Hydroelectric Cell is a 21st century phenomenal revolutionary invention to produce green electricity by water splitting at room temperature by oxygen-defects and nanopores deliberately created in metal oxides. HECs have been fabricated to produce green electricity by using mixture of red mud and iron oxide (RMFe). Splitting of water molecule heterolytically takes place on the cation-oxygen vacancy pair (M δ + -Vo δ −) present on the surface of RM and RMFe pellets. It has been observed from the Williamson-Hall, plots and Photoluminescence analysis that RMFe particles exhibit large strain and defects due to inter-ionic diffusivity of different metal cations. More hetero-ionic pairs of Fe 3+ -Vo δ-, Ca 2+ -Vo δ- and Al 3+ -Vo δ- present on the RMFe surface increase the adsorption and chemidissociation of water. The RM and RMFe based HECs have delivered 7 mA and 17 mA peak current and voltage 0.8 V and 1.02 V. Red mud utilization in the fabrication of Hydroelectric Cell is a significant step towards waste management and wealth creation. Graphical Abstract: ga1 Highlights: A cleanest solution in the mitigation of huge industrial waste red mud fabricated as hydroelectric cell to generate green energy. Electricity is generated by dissociating water at room temperature without using any electrolyte/acid/photon/temperature. Redmud hydroelectric cell generated short circuit current 17 mA, and 1.02 V open cell voltage. An estimation of 0.33 MT of red mud can be utilized to generate 100 MW power by fabricating its hydroelectric cell.